2019
DOI: 10.1021/acs.analchem.9b00681
|View full text |Cite
|
Sign up to set email alerts
|

A Field Procedure To Screen Soil for Hazardous Lead

Abstract: Soils retain lead contamination from possible sources such as mining, smelting, battery recycling, waste incineration, leaded gasoline, and crumbling paint. Such contamination is often concentrated in toxic hot spots that need to be identified locally. To address this need, a simple field procedure was designed to screen soil for hazardous Pb for use by the general public. The procedure is a modification of the in vitro soil Pb extraction described by Drexler and Brattin (Hum. Ecol. Risk Assess.2007, 13, 383) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Recent work has shown that XRF analysis of Pb in liquid extracts highly correlates with analysis by inductively coupled plasma mass spectrometer (ICP-MS; Landes et al, 2019), which was also seen for samples analyzed in the present study ( Figure S1 in the supporting information). Concentrations of Pb in water samples were analyzed in the laboratory by high-resolution ICP-MS (Thermo Scientific Element II); all fieldprocedure extracts were also analyzed by ICP-MS for confirmation.…”
Section: Instrumental Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…Recent work has shown that XRF analysis of Pb in liquid extracts highly correlates with analysis by inductively coupled plasma mass spectrometer (ICP-MS; Landes et al, 2019), which was also seen for samples analyzed in the present study ( Figure S1 in the supporting information). Concentrations of Pb in water samples were analyzed in the laboratory by high-resolution ICP-MS (Thermo Scientific Element II); all fieldprocedure extracts were also analyzed by ICP-MS for confirmation.…”
Section: Instrumental Analysissupporting
confidence: 81%
“…The main difference of the field procedure used in this study relative to the later version described in Landes et al (2019) is that a test strip impregnated with sodium rhodizonate was inserted directly into the unfiltered solution after the extraction time of 1 hr instead of adding a gelatin capsule of sodium rhodizonate to the filtered extract (Landes et al, 2019). The procedure was later modified because we noticed that the Plumbtesmo® rhodizonate strips degraded with temperature and sunlight.…”
Section: Field Procedures To Screen Soil Pb Used By Parentsmentioning
confidence: 99%
See 3 more Smart Citations